The Impact of the Internal Conflicts of Brutus toward His Life in “Julius Caesar” by Shakespeare - Aulia Putri (English Department, University of Riau Kepulauan, Batam,Indonesia, 2015)
The writer chose the literary work of Shakespeare entitled Julius Caesar to be analyzed. In this literature, the writer noticed that the character of Brutus who was also a friend of Julius Caesar was willing to kill his closest friend. The writer was interested in analyzing this side of Brutus. Brutus was well known as a wise and honest man but could commit a crime. Brutus did not want Rome to turn into imperial Rome which was originally a Republican state. Further, the writer analyzed the internal conflicts experienced by Brutus and its effects toward Brutus’ life. In analyzing this thesis, the writer used the psychological approach with the theory of psychoanalysis; Human Psycho Zone by Sigmund Freud consisted of id, ego, and superego. The writer analyzed the internal conflicts experienced by Brutus, namely: his blindness to reality and his idealism that did not provide a benefit for him. These conflicts had negative impacts to the end of Brutus’ life after killing Julius Caesar. The negative impacts in the life of Brutus namely: Brutus' wife suffered severe depression since Brutus became a murderer, Brutus felt inferior and loss his self-esteem, and destroys him. Based on the analysis conducted by the writer, the id of Brutus was more dominant than the superego. The id of Brutus dominated in any actions that Brutus did, especially for dealing with conflicts within himself.Key Words: Internal Conflict; Human Psycho Zone; and Impact